Increasing Farmers' Competence Through Training In Organic Fertilizer Production To Increase Plant Growth - Timisela, Stephanny Inagama; -, La Maga; Titalessy, Pisi Bethania; Antoh, Agustina Ester; Mulyono, Herlina Irianti; Palloan, Angga Frediyanto (Asia Pacific Journal of Management and Education (APJME), 2024)
In order for agricultural crop cultivation activities to be carried out sustainably, efforts must be made to maintain or increase soil fertility. Organic matter has a very important role in maintaining soil fertility. The application of organic materials can be mature organic materials such as organic fertilizer. Considering the benefits of using compost that comes from organic materials, it is important for all farms to implement it. The location for implementing community service will be in Yobeh Village, Sentani District, Jayapura Regency City. The targets for training activities are farmers in Yobeh Village. The tools and materials used in training on making compost consist of: EM-4 solution, water, forage or straw, husks, buckets, scoops, knives or scissors. This community service activity is carried out using several methods, namely lecture methods, training methods and assistance to participants regarding the obstacles faced in making compost fertilizer.